Cartoon 4: Evaluation - page 1 (in Chinese) - Novossiolova, Tatyana; Dando, Malcolm; Shang, Lijun; Xue, Yang (2021)
This cartoon - the first of two - is about the development of an institutional research process in biological and chemical security education in the Higher Education sector.